Extension of anticoagulation after venous thromboembolism - Schulman, S. (Hämostaseologie, 2008)
Whereas every clinician agrees on the need for anticoagulation initially after the diagnosis of venous thromboembolism (VTE), the opinions regarding optimal duration of secondary prophylaxis differ. The decision is complicated by the large number of identified risk factors associated with the risk of recurrence. In addition consideration has to be taken to the risk factors for bleeding and individual patient preferences. Data from long-term follow-up studies up to a decade indicate that some risk factors for recurrence decline and others seem to gain importance with time. In this review data has been extracted from the most illustrative trials to highlight controversies but also where there is consensus in order to give the clinician some support for the individual decisions on extension of anticoagulation after VTE.
Keywords: Venous thromboembolism; risk factors; recurrence; bleeding